2022
DOI: 10.1371/journal.pone.0264193
|View full text |Cite
|
Sign up to set email alerts
|

Community pharmacists’ attitudes toward practice-based research and their perceived utilization of scientific evidence

Abstract: Background Enhancing the contribution of practicing pharmacists into scientific evidence via practice-based research (PBR) is crucial in maintaining high-quality clinical practice and healthcare delivery. Involving community pharmacists in PBR can potentially can also help break barriers to the utilization of the current best evidence in everyday pharmacy practice. The impact of pharmacists’ attitude towards PBR on their utilization of current best evidence in pharmacy practice is understudied. Objectives Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Very little attention has been paid to community pharmacists' information needs for evidence-based self-medication counselling. Up to now, research has tended to focus more on investigating barriers, educational interventions and the status quo of counselling-practice [9,12,13,19,20,41]. This study was therefore set out with the aim of gaining an insight into their information needs to help facilitate EbPharm into practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Very little attention has been paid to community pharmacists' information needs for evidence-based self-medication counselling. Up to now, research has tended to focus more on investigating barriers, educational interventions and the status quo of counselling-practice [9,12,13,19,20,41]. This study was therefore set out with the aim of gaining an insight into their information needs to help facilitate EbPharm into practice.…”
Section: Discussionmentioning
confidence: 99%
“…Previously published studies have shown, however, that external evidence in particular is only sparsely integrated into everyday counselling [9][10][11][12][13][14][15][16][17][18]. Barriers such as a lack of time, and missing information resources were identi ed as the main reason causing the evidence-to-practice-gap [19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Little attention has been paid to their information needs for evidence-based self-medication counselling. Previous research mainly focused on investigating barriers, educational interventions and the status quo of counselling practice [ 9 , 12 , 13 , 19 , 20 , 42 ]. This study set out with the aim of gaining an insight into their information needs in five predefined areas to help implement EbPharm into practice.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from external evidence, the pharmacist's practical experience and the patient's preference should be considered when counseling [6,7]. However, a lack of information sources, time, and search skills has been identified as common barriers to EbPharm [8][9][10][11][12][13][14][15][16][17][18]. Consequently, various evidence-based information resources were introduced to reduce the evidence-to-practice gap.…”
Section: Introductionmentioning
confidence: 99%